Reclassifying Papillary, Oncocytic and Chromophobe Renal Tumours Based on the 5thWho Classification 2022 - Nilofar SHAIKH; Mary MATHEW (Federation of Turkish Pathology Societies, 2024)
Objective: The classification of renal tumors is expanding with the addition of new molecular entities in the 5th World Health Organization classification. Apart from this, the major updates in the definition of papillary renal cell carcinoma are that these tumors are no longer subtyped into type 1 and type 2. In oncocytic tumors, the new molecularly defined renal tumors, emerging and novel entities need to be considered in the diagnosis of oncocytic and chromophobe renal tumors. Material and Methods: This is a retrospective study to review and reclassify papillary, oncocytic, and chromophobe renal tumors based on the new WHO classification and correlate with clinical data, gross, microscopic features, and immunohistochemistry markers. Results: A total of thirteen cases were reviewed and the tumor grade was changed for three out of four cases of papillary renal cell carcinoma and a single case was recategorized and graded. In nine cases of oncocytic and chromophobe renal tumors, the diagnoses were modified in 3 cases. Conclusion: Newly defined molecular renal tumors require advanced immunohistochemistry markers and molecular tests. This poses diagnostic challenges to pathologists practicing in low resource settings where molecular tests are not available.